THE IMPORTANCE OF WATER QUALITY OF ANIMAL WATERING - PEREIRA, EDILAINE REGINA; PATERNIANI, JOSÉ EUCLIDES STIPP; DEMARCHI, JOÃO JOSÉ ASSUMPÇÃO DE ABREU (Revista Brasileira de Engenharia de Biossistemas, 2009)
Actually the world population is dependent of activities that turn around the water in: basic sanitation,farming production, energy generation, industry activity, transport and leisure. In the industry of animalproduction intensive characteristics, it is of basic importance the rational use of the water of goodquality. The water must be considered as an essential nutrient and when used in the animal in a drinkform, the use of the water with bad quality can intervene in the indices zootécnicos and the disseminationof diseases, causing serious economic damages, beyond takes agent pathogenic of interest in publichealth. Being thus, the water can be and must be considered the most important potential element ofthe sanitary hygienical actions, since that there is an efficient treatment.